Role of immunotherapy in treatment refractory chordomas: review of current evidence - Alexander, A. Yohan; Dhawan, Sanjay; Venteicher, Andrew S. (Frontiers in Surgery, 2024)
Chordomas are aggressive tumors that are thought to arise from remnants of the embryological notochord. They can arise along the ventromedial aspect of the sacrum, mobile spine, and clivus with most cases occurring in the sacrum or skull base. Despite surgery and radiation, chordomas often progress and become refractory to further treatment. The high recurrence rate has created an urgent need to develop new systemic treatment options. Recent case reports and clinical trials have highlighted the use of immunotherapy for refractory chordomas. In this review, we summarize the results of these studies and discuss the potential role of immunotherapy for chordomas.The PUBMED database was queried for studies mentioning both "Chordoma" and "Immunotherapy." All case series and case reports that involved administration of an immunotherapy for chordoma were included. Additional studies that were found during literature review were added. ClinicalTrials.Gov was queried for studies mentioning both "Chordoma" and "Immunotherapy." The final cohort consisted of all clinical trials that utilized immunotherapy for chordomas of any location.Eight case reports and series of immunotherapy for treatment refractory chordoma were identified.Most patients received immunotherapy targeting the PD-1/PD-L1 interaction, and two patient received therapy targeting this interaction along with the tyrosine kinase inhibitor pazopanib. One patient received a vaccine derived from autologous tumor cells, and one patient received a viral vector that downregulated the effect of TGF-beta. One clinical utilized a brachyury vaccine in conjunction with standard of care radiotherapy.Immunotherapy for chordoma is a promising area of investigation with increasing, but small, numbers of case series and clinical trials. Despite challenges in patient accrual, future directions in chordoma immunotherapy may lie in vaccine-based therapies and immune checkpoint inhibitors. Understanding chordoma heterogeneity and microenvironment will likely elucidate important chordoma features that will inform future clinical trial design.